Heritage Multimedia and Children Edutainment: Assessment and Recommendations - Naif A. Haddad (Advances in Multimedia)
Despite the rising commodification of heritage sites and practices, children engagement in their own cultures remains incredibly low, greatly endangering the future preservation of nations’ unique nonrenewable resource. Considering children’s very early engagement with cultural attitudes and identities, it is increasingly critical to develop a deeply rooted culture of responsibility and conservation from the earliest years, ensuring that children naturally feel invested in their surroundings. Unfortunately, heritage education remains largely undervalued, with most efforts relying on in-person experiences in formal cultural institutions. This paper thus aims to explore how heritage education can be redefined, using some of the most innovative virtual imaging and artificial reality technologies to at once expand access and engagement with one’s own history. Though there have been introductory applications of this edutainment multimedia technology, it will require a multidisciplinary team to create heritage programming which is as entertaining as it is intellectually challenging for young children. With the rich resources of 3D imaging and interactive programming already at our disposal, we are well-equipped to do so, given a coordinated effort.